Pengaruh Terapi Kombinasi Dzikir Dan Aromatherapy Terhadap Kecemasan Pada Pasien Yang Menjalani Hemodialisa: Case Study - Desy Purnama Sari; Erna Rochmawati; Akhmad Zuhri (STIKES Columbia Asia Medan, 2024)
Impaired kidney function accompanied or without a decrease in GFR that has lasted more than three months is also called chronic kidney failure. Chronic kidney failure causes physiological and psychological impacts such as anxiety. The most common management of CRF is hemodialysis. Hemodialysis therapy can cause discomfort that affects psychological such as the emergence of feelings of anxiety, where the feeling arises because you have to visit the hemodialysis unit regularly and feelings of worry related to unpredictable health conditions. This study used a case study methoddoe whose purpose was to determine the effect of dhikr and aromatherapy combination therapy on the anxiety of patients undergoing hemodialysis. The instrument of this study used the ZSAS (Zung-Self Anxiety Rating Scale) questionnaire. The results of the case study showed that patients experienced mild anxiety with a score of 45 and after being given intervention for 2 meetings, a score of 37 was obtained which means not anxious. Combined therapy of dhikr and aromatherapy is a therapy that can provide calm. In conclusion, there is an influence in the provision of dhikr and aromatherapy combination therapy in those undergoing hemodialysis.